Tren Penelitian Global Implementasi Bimbingan dan Konseling Islam Kontemporer: Kajian Literatur: Global Research Trends in the Implementation of Contemporary Islamic Guidance and Counseling: A Literature Review - Muhammad Fikri Fauzi; Puji Maulana; Faisol Hakim; Akhmad Rudi Masrukhin; Asna Asna; Moch Arifudin (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The implementation of guidance and counseling services is relevant to the Islamic world, leading to the development of Islamic guidance and counseling services that emphasize religious and spiritual aspects. Characters formed through Islamic guidance and counseling exhibit traits such as self-reflection, patience, sincerity, and earnest effort. This study aims to analyze global trends in Islamic guidance and counseling research. This study uses a systematic literature review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method, with the keyword 'Islamic Guidance and Counseling' from 2016 to 2025, using the Dimension AI database for its broad coverage, and visualizations from the VOSviewer application for material enrichment. The results show a fluctuating trend in the publication of scientific articles, with 3 publications in 2016, 482 in 2021, and 341 in 2025. Reflections from the VOS Viewer include network visualization, overlay visualization, density visualization, co-occurrence, and co-authorship network visualization. There are 15 clusters with a minimum of 3 mentions in the VOS Viewer application, totaling 532 items, such as character traits, counseling, inclusive education, Islamic counseling, and school counseling. Meirinawati Meirinawati from the State University of Surabaya, Indonesia, with 41 publications, is an active author in related articles, while the active journal in related publications is Jurnal Publika with 283 publications. The results of this study provide insight into the global research trend in 'Islamic Guidance and Counseling,' enriching the information and data available to experts in counseling and encouraging further research on the virtues of Islamic guidance and counseling.